Post-traumatic Stress Disorder (PTSD) and Coping Strategies: A Case Study of a Family of a War Stricken Soldier - Gado, Gamal Abdulhamed (Advances in Social Sciences Research Journal, 2020)
The current study aimed to knowing the level of PTSD among a family of a War Stricken Soldier (the wife and eldest daughter), and knowing the clinical indications for PTSD symptoms to the cases, also it aimed to search about the coping strategies which the wife and the eldest adopted and study the effect of these coping strategies on relieving PTSD symptoms, and it aimed to knowing the dynamic motivations for the cases responses on the TAT cards, that underlie the emergence of PTSD symptoms and the adoption of specific coping strategies. Several tools were used, Semi Structured interview, Thematic Apperception Test (TAT), Davidson Scale for Post-Traumatic Stress, Post-Traumatic Coping Strategies Scale. The study results indicated to the existence of mild level on PTSD to the wife, and moderate level to the daughter, Problem-solving strategies have emerged as the wife's strongest coping strategies, and avoidance strategies have emerged as the daughter's strongest coping strategies. The responses of the two cases on TAT and the analysis of their latent dynamic motivations are discussed.